Family Issues on Marriage, Divorce, and Older Adults in Japan: With Special Attention to Regional Variations - Kumagai, Fumie (Springer, 2015)
This book provides insightful sociological analyses of Japanese demography and families, paying attention not only to national average data, but also to regional variations and community level analyses. In analyzing Japanese family issues such as demographic changes, courtship and marriage, international marriage, divorce, late-life divorce, and the elderly living alone, this book emphasizes the significance of two theoretical frameworks: the dual structure and regional variations of the community network in Japan.